The C-Terminal Transactivation Domain of STAT1 Has a Gene-Specific Role in Transactivation and Cofactor Recruitment - Parrini, Matthias; Meissl, Katrin; Ola, Mojoyinola Joanna; Lederer, Therese; Puga, Ana; Wienerroither, Sebastian; Kovarik, Pavel; Decker, Thomas; Müller, Mathias; Strobl, Birgit (Frontiers in Immunology, 2018)
STAT1 has a key role in the regulation of innate and adaptive immunity by inducing transcriptional changes in response to cytokines, such as all types of interferons (IFN). STAT1 exist as two splice isoforms, which differ in regard to the C-terminal transactivation domain (TAD). STAT1β lacks the C-terminal TAD and has been previously reported to be a weaker transcriptional activator than STAT1α, although this was strongly dependent on the target gene. The mechanism of this context-dependent effects remained unclear. By using macrophages from mice that only express STAT1β, we investigated the role of the C-terminal TAD during the distinct steps of transcriptional activation of selected target genes in response to IFNγ. We show that the STAT1 C-terminal TAD is absolutely required for the recruitment of RNA polymerase II (Pol II) and for the establishment of active histone marks at the class II major histocompatibility complex transactivator (CIIta) promoter IV, whereas it is dispensable for histone acetylation at the guanylate binding protein 2 (Gbp2) promoter but required for an efficient recruitment of Pol II, which correlated with a strongly reduced, but not absent, transcriptional activity. IFNγ-induced expression of Irf7, which is mediated by STAT1 in complex with STAT2 and IRF9, did not rely on the presence of the C-terminal TAD of STAT1. Moreover, we show for the first time that the STAT1 C-terminal TAD is required for an efficient recruitment of components of the core Mediator complex to the IFN regulatory factor (Irf) 1 and Irf8 promoters, which both harbour an open chromatin state under basal conditions. Our study identified novel functions of the STAT1 C-terminal TAD in transcriptional activation and provides mechanistic explanations for the gene-specific transcriptional activity of STAT1β.